Determination of 10 pesticides, newly registered in Egypt, using modified QuEChERS method in combination with gas and liquid chromatography coupled with tandem mass spectrometric detection. Issue 3 (19th February 2019) - Soliman, Mostafa; Khorshid, Mona A.; El-Marsafy, Ashraf M.; Abo-Aly, Mohamed M.; Khedr, Tawfeek
ABSTRACT: The analysis of pesticide residues in food is currently an increasingly important task. In this work, a rapid and sensitive protocol has been developed for the determination of ametoctradin, amisulbrom, bromoxynil-octanoate, chlorantraniliprole, cyhalofop-butyl, hymexazol, metaldehyde, prodiamine (dithiopyr), sulcotrione and tolfenpyrad. The extraction was done using the citrate buffer acetonitrile-based QuEChERS (quick, easy, cheap, effective, rugged and safe) sample preparation technique. Acetonitrile extracts were directly injected into the liquid chromatography-tandem mass spectrometry system, and solvent exchange was used prior to the injection in the gas chromatography system. Different exchange solvents were evaluated and a mixture of n-hexane:acetone (9:1) was chosen. Matrix effects were evaluated and a relation between the signal suppression/enhancement and the co-extracted matrix was established. The validation study was carried out on cucumber, banana and lemon matrices following SANTE/11813/2017 of the European quality control guidelines. The precision and trueness of the method were determined from recovery experiments on six replicates of spiked blank samples at 0.01, 0.05, and 0.1 mg/kg for each commodity. The range of the obtained recoveries was 70–111%, with RSD values of <18% for all the tested concentrations. The only exception was hymexazol at 0.01 mg/kg in banana and cucumber.